Application of the Conceptual Model of Buddhist Counseling and Guidance Through Online Media During the Covid 19 - Sulaiman Girivirya (Faculty of Teacher Training and Education, Mulawarman University, 2021)
The foundational teaching of the four noble truths is the foundation of the Buddhist counseling psychology conceptual paradigm. The Four Noble Truths are the most fundamental teachings of Buddhism, and both Mahayana and Theravada Buddhists subscribe to them. This model is applied in the form of training by measuring prior concept knowledge and training. After a final exam was done at the implementation of the program's second session, the participants of the application